Analysis of customer activity, the importance of timing for effective marketing actions: Case of group buying site, grouper - Nina Angelovska (UTMS Journal of Economics, 2021)
In order to achieve successful management of their sales and marketing activities companies need to monitor and analyse the activity of their customes. The goal of this study is twofold. First, an empirical investigation of customers' activitiy is conducted by using the Customer Activity measures (Kumar and Reinartz 2012), and in addition a new measure is introduced to determine when a customer ceases to be a customer and the relationship with him ends, and when a customer becomes "currently inactive" before he reactivates again. Second, by having information on the status of the customer's activity, the implementation of appropriate marketing actions is investigated. Information and results gained from this analysis can be a base for action, tools for rehabilitation of "currently inactive customers" are provided that can be used by e-shops and marketplaces. Each company, can use the Customer activitiy measures that are suitable, depending on the industry in which it operates, in order to create a comprehensive image of its customers's activity, increase their activity and make appropriate marketing decisions.
Keywords: M30; 330; CRM strategy; customer-centric strategy; customer retention; lifetime duration; North Macedonia